Red velvet cupcake murder ebook - Fluke, Joanne (Hannah Swensen Mystery, 2013)
"If your reading habits alternate between curling up with a good mystery or with a good cookbook, you ought to know about Joanne Fluke."— Charlotte Observer This summer has been warmer than usual in Lake Eden, Minnesota, and Hannah Swensen is trying to beat the heat both in and out of her bakery kitchen. But she's about to find out the hard way that nothing cools off a hot day like a cold-blooded murder. At the grand opening of a local hotel, a police department employee nearly dies falling from a penthouse—and then another woman, with whom Hannah has a less-than-friendly relationship, winds up dead. Hannah is the prime suspect—and to clear her own name, she's got to find out who iced the victim... Features cookie and dessert recipes from The Cookie Jar, including Red Velvet Surprise Cupcakes and Chocolate Covered Peanut Cookies! "Culinary cozies don't get any tastier than this winning series."— Library Journal "Loaded with mouthwatering recipes and clever plotting, the latest Hannah Swensen mystery delights."— RT Book Reviews